2012
DOI: 10.1590/s1806-66902012000200022
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros genéticos para a produção de leite em caprinos das raças Saanen e Alpina

Abstract: *Resumo -Objetivou-se com este trabalho estimar parâmetros genéticos para a produção de leite acumulada até os 305 dias (P305) de cabras das raças Saanen e Alpina. Foram utilizadas as duas primeiras parições de cabras pertencentes a rebanhos participantes do programa de controle produtivo e reprodutivo de caprinos (PROCAPRI) da UNESP-FCAV-Jaboticabal-SP. A P305 foi analisada por meio de modelos de repetibilidade e bicaracterísticas. Para verificar a influência dos efeitos fixos sobre a característica analisada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
1
6
0
2
Order By: Relevance
“…These values are higher than the reported by Facó et al (2007) who worked with Anglo Nubian dairy goats in a semi-intensive system and observed a lactation length of approximately 141 days. However, the lactation length observed in this study was lower than Alpine and Saanen goats in southeastern region (211 days) (Irano et al, 2012). If it was compared the results with those reported by Santos and Santana (2011), who found LL averages of 168 and 251 days for the Anglo Nubian and Saanen breeds, respectively, it appears that the survey means follow the trend of genotypes.…”
Section: Resultssupporting
confidence: 44%
“…These values are higher than the reported by Facó et al (2007) who worked with Anglo Nubian dairy goats in a semi-intensive system and observed a lactation length of approximately 141 days. However, the lactation length observed in this study was lower than Alpine and Saanen goats in southeastern region (211 days) (Irano et al, 2012). If it was compared the results with those reported by Santos and Santana (2011), who found LL averages of 168 and 251 days for the Anglo Nubian and Saanen breeds, respectively, it appears that the survey means follow the trend of genotypes.…”
Section: Resultssupporting
confidence: 44%
“…The values were weighted by the number of goats (100) used to estimate these weights because ZPLAN requires economic values relating to a dam without considering the time and amount of expression in later generations. Mean values of traits and their standard deviations (Table 3) were calculated by Irano et al (2012), except for AFK and KI, which was reported by Lôbo and Silva (2005). The values for somatic cell count, dry milk solids, protein and fat content were estimated from the CAPRA-GENE databank.…”
Section: Economic Values and Genetic And Phenotypic Parametersmentioning
confidence: 99%
“…However, these means were estimated from one or a few flocks in a certain period of time stationary (single lactation, one year, etc.) or sample taken from the cooling tank (Ciffoni, 1998;Gonçalves et al, 2001Gonçalves et al, , 2002Irano et al, 2012;Ribeiro et al, 2000;Souza et al, 2009;Tholon, 2000). The averages obtained in this way are not sufficient to characterize a parameter of the population.…”
Section: Introductionmentioning
confidence: 99%